The effect of powder sintering method on the densification and microstructure of pewter alloys - Ariff, Tasnim Firdaus; Gabbitas, Brian Leslie; Zhang, Deliang (IOP Publishing, 2009)
Pewter alloys made from tin, copper and antimony powders were sintered using microwave and conventional vacuum sintering. Three different compositions of the pewter alloy were used; 91Sn6Cu3Sb, 94Sn4Cu2Sb and 97Sn2Cu1Sb. The effect of densification and microstructure of the pewter alloys from varying sintering time and sintering mode were examined and compared. Samples were compacted at 40kN and sintered at 220°C. Samples in the conventional furnace were sintered 60 minutes and 120 minutes, while samples in the microwave furnace were sintered for 15 and 30 minutes. Samples sintered at longer sintering times resulted in higher density for both sintering methods. Microwave sintering produced samples with slightly smaller grain size than the conventionally sintered samples resulting in a better densification. There were no new phases formed from the sintering of pewter alloy.